2015
DOI: 10.1186/s13089-015-0032-6
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of abdominal ultrasound for the diagnosis of pneumoperitoneum in patients with acute abdominal pain: a pilot study

Abstract: BackgroundPneumoperitoneum is a rare cause of abdominal pain characterized by a high mortality. Ultrasonography (US) can detect free intraperitoneal air; however, its accuracy remains unclear. The aims of this pilot study were to define the diagnostic performance and the reliability of abdominal US for the diagnosis of pneumoperitoneum.MethodsThis was a prospective observational study. Four senior and two junior physicians were shown, in an unpaired randomized order, abdominal US videos from 11 patients with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 17 publications
1
36
0
Order By: Relevance
“…23 It has been considered that air is hardly detected with US because the sound wave does not travel through the gas and leaves artefacts. Recently, these artefacts have gained diagnostic properties in detecting pneumoperitoneum, 28,29 as well as the detection of the air injected into the stomach through a nasogastric tube. 30 In a study by Moriwaki et al, 28 the sensitivity and specificity of US for detecting intraperitoneal free-air rose up to 85-100%.…”
Section: Discussionmentioning
confidence: 99%
“…23 It has been considered that air is hardly detected with US because the sound wave does not travel through the gas and leaves artefacts. Recently, these artefacts have gained diagnostic properties in detecting pneumoperitoneum, 28,29 as well as the detection of the air injected into the stomach through a nasogastric tube. 30 In a study by Moriwaki et al, 28 the sensitivity and specificity of US for detecting intraperitoneal free-air rose up to 85-100%.…”
Section: Discussionmentioning
confidence: 99%
“…However, a recent study showed that senior physicians with experience in abdominal US can rapidly learn to identify patterns suggestive of pneumoperitoneum with almost 90 % accuracy [ 20 ]. The study also indicated that a focused abdominal US exam comprising two views (epigastric and right hypochondrium) was similar in sensitivity and specificity to the full abdominal exam.…”
Section: Discussionmentioning
confidence: 99%
“…After removing irrelevant articles, 13 studies were read in full test. Finally, five studies were eligible for meta-analysis, [4][5][6][7][8] and the whole procedure of literature screening is shown in Figure 1.…”
Section: Study Identification and Characteristicsmentioning
confidence: 99%
“…Several studies with limited sample size reported the ability of ultrasonography in diagnosing of pneumoperitoneum. [4][5][6][7][8] But there was significant controversy among these studies. The aim of this meta-analysis was to explore the diagnostic value of ultrasound of pneumoperitoneum in emergent or critical conditions.…”
Section: Introductionmentioning
confidence: 99%